2020
DOI: 10.3390/ijms21176140
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Light at Night Increases Recruitment of New Neurons and Differentially Affects Various Brain Regions in Female Zebra Finches

Abstract: Despite growing evidence that demonstrate adverse effects of artificial light at night (ALAN) on many species, relatively little is known regarding its effects on brain plasticity in birds. We recently showed that although ALAN increases cell proliferation in brains of birds, neuronal densities in two brain regions decreased, indicating neuronal death, which might be due to mortality of newly produced neurons or of existing ones. Therefore, in the present study we studied the effect of long-term ALAN on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 57 publications
4
11
0
1
Order By: Relevance
“…Therefore, in that study we also recorded neuronal densities in several forebrain regions, and found that despite the increased proliferation, total neuronal densities decreased in some regions, suggesting net neuronal death. In a later study [7], in which we exposed female zebra finches to a longer ALAN exposure (six weeks), we recorded NR in these brain regions and found that ALAN increased recruitment compared to controls, possibly as a compensatory response to ALAN-induced neuronal death, and/or due to increased nocturnal locomotor activity caused by sleep disruption. In addition, the decrease in total neuronal densities, which we observed in some brain regions under short-term ALAN exposure [6], was not found under the longer exposure [7], indicating a temporal effect of ALAN.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Therefore, in that study we also recorded neuronal densities in several forebrain regions, and found that despite the increased proliferation, total neuronal densities decreased in some regions, suggesting net neuronal death. In a later study [7], in which we exposed female zebra finches to a longer ALAN exposure (six weeks), we recorded NR in these brain regions and found that ALAN increased recruitment compared to controls, possibly as a compensatory response to ALAN-induced neuronal death, and/or due to increased nocturnal locomotor activity caused by sleep disruption. In addition, the decrease in total neuronal densities, which we observed in some brain regions under short-term ALAN exposure [6], was not found under the longer exposure [7], indicating a temporal effect of ALAN.…”
Section: Introductionmentioning
confidence: 85%
“…Our study consisted of two experiments, a cell proliferation (CP) experiment, which included three groups with six male birds per group (Figure 1A), and a neuronal recruitment experiment (NR), which included two groups with eight male birds per group (Figure 1B). All of the following experimental conditions and procedures were identical to those in our previous studies with females [6,7]. Zebra finches were hatched and reared in our outdoors breeding colonies, at the I. Meier Segals Garden for Zoological Research at Tel-Aviv University, Israel.…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations